Arctic Cryosphere: Changes and Impacts - T. V. Callaghan; M. Johansson; T. D. Prowse; M. S. Olsen; L.-O. Reiersen (AMBIO, 2011)
The Arctic cryosphere is a critically important component of the earth system, affecting the earth's energy balance, sea level, greenhouse gases and atmospheric circulation, transport of heat through ocean circulation, ecology and human resource use and well-being. The Arctic cryosphere is, however, changing rapidly with multiple important consequences that will potentially affect the earth system including the human population. The drivers of changes in the Arctic's cryosphere, the recent and projected changes in the cryosphere and the consequences for future climate warming, sea level rise, ecology and human wellbeing, have been comprehensively assessed by the Arctic Council's Snow Water, Ice, and Permafrost in the Arctic (SWIPA) Project through its Arctic Monitoring and Assessment Programme Working Group. This article introduces the assessment and the associated papers within a special issue of the journal Ambio that extract and present some of the major findings of the SWIPA report.